STUDY OF TEST CASE PRIORITIZATION TECHNIQUE USING APFD - Gupta, Rahul; Yadav, Akhilesh Kumar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Regression testing is used to ensure that bugs are fixed and new functionality introduce in a new version of a software that don't adversely affect the original functionality inherited from the previous version.Regression testing is one of the most complaining activities of software development and maintenance.Unluckily, It may have feeble resources to allow for the re-execution of all test cases during regression testing. In this situation the use of test case prioritization is profitable because the best appropriate test cases are executed first. In this paper we are proposing an algorithm to prioritize test cases based on rate of fault detection and impact of fault.The proposed algorithm recognises the exhausting fault at earlier stage of the testing process.We are using an Average Percentage of Faults Detected (APFD) metric to determine the effectiveness of the new test case arrangements.